To the nature of 0+ states in 228Th studied by two-neutron transfer - A. I. Levon; P. Alexa; S. Pascu; V. A. Onischuk; P. G. Thirolf (Ядерна фізика та енергетика)
Sequences of states observed in the 230Th(p, t)228Th reaction are selected which can be treated as rotational bands and as multiplets of excitations. Moments of inertia have been derived from these sequences, whose values may be considered as evidence of the two-phonon nature of most 0+ excitations. Experimental data are compared with interacting boson model and quasiparticle-phonon model calculations and with experimental data for 229Pa. Conclusions have been made concerning the nature of 0+ states in 228Th.